PENDUKUNG KEBERHASILAN PENGELOLAAN SAMPAH KOTA - Hardiatmi, Sri - (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2011)
Abstract The existence people and their octivities in acity will still arise a bunch of pubbish wste here an there. The main supporting factors in managing the waste is the people active role. Because, Indeed, they them selves who produce thos waste so that they have to be responsible to over came every environmental problem caosed by those waste. The most surtable waste management is the concept of 4 R; Reduce, Reuse, Recycle and Replace. This concept has many advantages. They are : 1.Â Economically. The Recycle waste have higher economic value 2. Estetically. The proper waste management will make the town be more beautifull. 3.Â Health. The proper waste management will make town environment cleaner is will proper wate management will reduce the number of vaused waste in TPA. So it is not impossible that the land for TPA can be saved. Transportation. When the waste are maintained well there will not be needed more transportation to bring the rublaish in to the TPA. Supports from te local government and other department are needed to make this waste management work well and success Beside that another important factor is the active role of the people surround. Key words : rubbish town, 4 R concept application, peopleâ€™s active role.